Hubungan Antara Persepsi terhadap Layanan Bimbingan Belajar dengan Kemandirian Belajar Peserta Didik Sekolah Menengah Pertama - Saputra, Andika Ari; Astuti, Budi (Jurnal Kajian Bimbingan dan Konseling, 2018)
This study is intended to identify the correlation between perception on tutoring services and Junior High School students’ autonomy. This study was a correlational and expose facto study. The population of this study is the entire students of Sekolah Menengah Pertama Negeri 10 Yogyakarta amount to 506 students. Then, this study took 253 students as research sample which is determined by using proportional stratified random sampling. The data were obtained employing perception on tutoring services scale and students’ autonomy scale. Cronbach’s Alpha was used to examine the reliability and it obtained p = 0,743 for perception on tutoring services and p = 0,744 students’ autonomy. To analyze the data, we employes statistical analysis. The results confirm that between perception on tutoring services and students’ autonomy of Sekolah Menengah Pertama Negeri 10 Yogyakarta are positively correlated.